2002
DOI: 10.1042/bj3610525
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the tandem-pleckstrin-homology-domain-containing protein TAPP1 interacts with Ptd(3,4)P2 and the multi-PDZ-domain-containing protein MUPP1 in vivo

Abstract: PtdIns(3,4,5)P3 is an established second messenger of growth-factor and insulin-induced signalling pathways. There is increasing evidence that one of the immediate breakdown products of PtdIns(3,4,5)P3, namely PtdIns(3,4)P2, whose levels are elevated by numerous extracellular agonists, might also function as a signalling molecule. Recently, we identified two related pleckstrin-homology (PH)-domain-containing proteins, termed ‘tandem-PH-domain-containing protein-1’ (TAPP1) and TAPP2, which interacted in vitro w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 0 publications
3
94
0
Order By: Relevance
“…These adaptor proteins bind PI3K lipid products in vitro (22)(23)(24) and are recruited to the plasma membrane in vivo in a PI3K-dependent manner (20,25). Intriguingly, we found that, after BCR stimulation, these adaptor molecules are recruited with delayed and sustained kinetics as compared with Btk (21), and, unlike Btk, their recruitment is not inhibited by the lipid phosphatase SHIP (SH2-containing inositol phosphatase) (26).…”
mentioning
confidence: 71%
“…These adaptor proteins bind PI3K lipid products in vitro (22)(23)(24) and are recruited to the plasma membrane in vivo in a PI3K-dependent manner (20,25). Intriguingly, we found that, after BCR stimulation, these adaptor molecules are recruited with delayed and sustained kinetics as compared with Btk (21), and, unlike Btk, their recruitment is not inhibited by the lipid phosphatase SHIP (SH2-containing inositol phosphatase) (26).…”
mentioning
confidence: 71%
“…It is a multiple PDZ-containing protein, with 13 PDZ domains (Ullmer et al, 1998), and it is thought to be involved in the selective targeting and assembly of signalling complexes (Becamel et al, 2000). In polarized epithelial cells, it localizes to tight junctions through the Coxsackie and adenovirus receptor (Coyne et al, 2004), where it interacts with the members of the Claudin and JAM (junctional adhesion molecule) families and may be involved in cell polarity signalling, tight junction barrier function and osmotic stress responses (Hamazaki et al, 2001;Kimber et al, 2002;Jeansonne et al, 2003;Lanaspa et al, 2007).…”
Section: Other Pdz-containing Targets Of E6mentioning
confidence: 99%
“…By yeast two-hybrid screening, MUPP1 interacts with serotonin 5-hydroxytryptamine type 2C receptors (18,19), kinase negative c-Kit (20), the tandem plextrin homology domain protein (21), and the membrane-spanning NG2 proteoglycan (22).…”
Section: Identification Of Mupp1 As a Car Binding Partner-tomentioning
confidence: 99%